Preferred Learning Techniques among Bachelor’s Level Students - Neupane, Dasarath; Pant, Sagar; Bhattarai, Parshuram (Nepal Journal of Multidisciplinary Research, 2023)
Learning styles describe how individuals acquire, interpret, and assimilate knowledge differently. The effective use of learning styles is essential for effective classroom education. The three most popular learning styles are kinaesthetic, auditory, and visual. This study pursued to learn more about the preferred learning modes of college students. There were 152 respondents from Baneshwor Multiple Campus, Kathmandu Nepal. The data were collected from first year students of BBS, B.Ed. and BA. The researchers used a scale of learning styles (VAK) with 28 items to accomplish the study's goal, and after confirming its validity and reliability, it was applied to the sample. The results show that there are no statistically significant differences in the types of learning patterns preferred by students. Based on these findings, the study recommends that teachers are encouraged to diversify college teaching strategies and methods to suit the preferred learning styles of their students, particularly new students, in order to motivate them to learn in the college environment and to provide the training needs and requirements necessary to enable them to take individual differences among their students into account when identifying educational goals.